Three step synthesis of single diastereoisomers of the vicinal trifluoro motif - Brunet, Vincent A.; Slawin, Alexandra M. Z.; O'Hagan, David (Beilstein Journal of Organic Chemistry, 2009)
A three step route to single diastereoisomers of the vicinal trifluoromethyl motif is described. The route starts from either syn- or anti-α,β-epoxy alcohols and takes a direct approach in that each of the three steps introduces a fluorine atom in a regio- and stereo-specific manner. Starting from either the syn- or the anti-α,β-epoxy alcohol, stereospecific reactions generate two separate diastereoisomeric series of this motif. The route is a significant improvement on an earlier six step strategy.
Keywords: C–F bond; organo–fluorine chemistry; stereospecific fluorination; vicinal trifluoro motif